Effects of large herbivore grazing on grasshopper behaviour and abundance in a meadow steppe - Zhu, Hui; Nkurunziza, Venuste; Wang, Jingting; Guo, Qinfeng; Ruan, Hang; Wang, Deli (Ecological entomology, 2020)
1. Adaptive phenotypic plasticity has been a major subject in evolutionary ecology, but how a species' behaviour may respond to certain environmental change is still not clear. In grasslands worldwide, large herbivores are increasingly used as a tool for grazing management, and occur to interact with grasshoppers that dominate grassland insect communities. Previous studies have been well‐documented about grazing effects on diversity and abundance of grasshoppers. Yet, how grazing may alter grasshopper behaviour, and potential effects on their abundance remains elusive. 2. We conducted a field experiment by manipulating grazing using sheep, cattle, and their mix to examine the behavioural responses and abundance of the grasshoppers (Euchorthippus unicolor) to grazing in a Leymus chinensis‐dominated grassland. 3. Results showed that the grasshoppers spent less time on feeding and resting on grasses, but more time on switching and resting on forbs under cattle grazing and mixed grazing with cattle and sheep. In contrast, the grasshoppers spent more time on feeding but less time on switching and resting on forbs under sheep grazing. The behavioural changes were also potentially linked to grasshopper abundance in the context of grazing management. 4. The responses of grasshopper behaviour and abundance to grazing may be largely triggered by altered vegetation and microclimates. Such behavioural flexibility of grasshoppers must be considered when large herbivores are recognised as a management tool for influencing grasshopper abundance, and grazer species should be paid more attention both individually and jointly for better grassland conservation. Grasshoppers have behavioural flexibility to adapt to grazing by different large herbivore assemblages. These behavioural changes are potentially linked to grasshopper abundance in the context of grazing. The responses of grasshopper behaviour and abundance to grazing may be largely triggered by altered vegetation and microclimates.